(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
According to the innovators, it is impossible to educate the current generation in this way in the new conditions, when the classical literary pedagogical theories have become obsolete. This is the general situation in the current pedagogical discipline. In this case, innovation is a very important pedagogy - a system of knowledge, the main characteristics of which are objectivity, expediency, consistency, non-contradiction. The system of pedagogy, like any other scientific theory, is designed and maintained by the principles that make up the system, that is, the system is based on basic knowledge, the only requirement of objectivity is that the level is adequate.